1995
DOI: 10.1007/bf00400717
|View full text |Cite
|
Sign up to set email alerts
|

The NSY mouse: a new animal model of spontaneous NIDDM with moderate obesity

Abstract: SummaryThe NSY (Nagoya-Shibata-Yasuda) mouse was established as an inbred strain of mouse with spontaneous development of diabetes mellitus, by selective breeding for glucose intolerance from outbred Jcl:ICR mice. NSY mice spontaneously develop diabetes mellitus in an age-dependent manner. The cumulative incidence of diabetes is 98 % in males and 31% in females at 48 weeks of age. Neither severe obesity nor extreme hyperinsulinaemia is observed at any age in these mice. Glucose-stimulated insulin secretion was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 29 publications
4
94
1
Order By: Relevance
“…We are surprised that there is not compensation for insulin deficiency with the single copy of Ins1 and with two copies of Ins1. However, a strain derived from the same colony as the NOD mouse, the NagoyaShibata-Yasuda mouse [9,10], a model of type 2 diabetes, which may share background genome with NOD [11,12], has no compensational hypertrophy of pancreatic islets despite increasing insulin resistance with ageing [9]. In addition, Kulkarni et al reported the importance of background genome in the induction of type 2 diabetes [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are surprised that there is not compensation for insulin deficiency with the single copy of Ins1 and with two copies of Ins1. However, a strain derived from the same colony as the NOD mouse, the NagoyaShibata-Yasuda mouse [9,10], a model of type 2 diabetes, which may share background genome with NOD [11,12], has no compensational hypertrophy of pancreatic islets despite increasing insulin resistance with ageing [9]. In addition, Kulkarni et al reported the importance of background genome in the induction of type 2 diabetes [13].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that greater insulin resistance for male mice with marginal insulin production leads to hyperglycaemia. In fact, most animal models of type 2 diabetes (including NagoyaShibata-Yasuda mice) show a high prevalence of type 2 diabetes in male mice [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Tests of glucose metabolism in type 2 diabetes NSY mice Male NSY mice weighing 25-28 g were purchased from Japan SLC (Hamamatsu, Japan) [21]. A single mouse was housed per cage, with a light-dark cycle of 12 h each (light from 07.00-19.00 h), and free access to food and water.…”
Section: Real-time Rt-pcr Analysismentioning
confidence: 99%
“…d Atorvastatin treatment at days 1-5 of culture reduced levels of the adipocyte differentiation-related transcription factors PPARγ and C/EBPα, and these effects were partially prevented by co-administration of 10 μmol/l GGPP we next examined the possible impact of these effects on in vivo glucose metabolism using NSY mice. This mouse reportedly exhibits moderate levels of obesity, insulin resistance and impaired insulin response to glucose [21], and is therefore considered a model for human type 2 diabetes. We placed NSY mice on regular diet (control group) or one containing atorvastatin (ATR group) from 5-20 weeks of age.…”
Section: Effects Of Atorvastatin On Glucose Metabolism and Slc2a4 Expmentioning
confidence: 99%
“…The NSY mouse closely mimics human Type II diabetes in that the onset is agedependent, the animals are not severely obese, and both insulin resistance and impaired insulin response to glucose contribute to disease development [7]. Impaired insulin response to glucose is observed after 12 weeks of age in this strain, and this impairment progressively worsens with advancing age [7]. Although impaired insulin response to glucose seems to play an important part in the development of Type II diabetes in this strain, impaired insulin action possibly also contributes to glucose intolerance.…”
mentioning
confidence: 99%